The awareness of halal products and services among Muslim consumer in Klang, Selangor / Ahla Majidah Janudin - Janudin, Ahla Majidah (2022)
The preference of halal products and services is an important aspect of every Muslim consumer's life that must be taken seriously. As explained in the Qur’an and the Sunnah, Islam has established clear guidelines and rules about halal and haram. In Islam, a Muslim must have a thorough understanding of halal in order to ensure that their products are used in a halal and ethical way. In Malaysia, the halal industry is handled by JAKIM and assisted by other organizations. However, there are some issues or challenges arise that have a negative impact on the development of the halal industry in Malaysia. For example, there are doubts among Muslim consumers about the halal status of products. In other words, Muslim consumers are increasingly exposed to various products that are suspected of being mixed with elements that are prohibited under Islamic law. Therefore, this study was conducted to find out the awareness of halal products and services among Muslim consumer in Klang, Selangor. There are two objectives in this study. First, to study the awareness level of Muslim consumer among Klang residents about halal products and services. Secondly, to identify the factors influencing Muslim consumer in buying halal products and services among Klang residents. The method that has been applied in this study is quantitative method where questionnaires have been distributed to 133 Muslim consumers in Klang, Selangor. The results have been analysed using the descriptive statistics to know the value of frequency, mean, standard deviation and percentage. The result from this analysis also used the IBM SPSS statistics version 20 program. The finding in this study shows that, Muslim consumers in Klang have good knowledge about halal and positive behaviour when choosing halal goods and services, where the mean score for the majority items show the highest mean value. The implication of the study is to see the level of awareness of Muslim consumers about halal products and services. I hope that this research will contributes to the development of halal industry in Malaysia and became the new economic growth in the future.